Rectus sternalis - Varun Rajesh Sarodaya; Tanveer Abdul Majeed (Wolters Kluwer Medknow Publications, 2017)
The sternalis muscle is an uncommon variant of the anterior thoracic chest wall musculature. During mastectomy of a patient, we observed a left-sided unilateral vertical band of texture sternalis muscle fiber overlying the lateral edge of the sternum. We are reporting about the same in this case. The origin of this muscle is a debatable topic. It can be misdiagnosed by the clinicians on a routine mammography. The presence of this muscle can cause alterations in electrocardiography during investigation.